The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.pbb.2013.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic activity of piracetam: Effect on cytokine production and oxidative stress

Abstract: Piracetam is a prototype of nootropic drugs used to improve cognitive impairment. However, recent studies suggest that piracetam can have analgesic and anti-inflammatory effects. Inflammatory pain is the result of a process that depends on neutrophil migration, cytokines and prostanoids release and oxidative stress. We analyze whether piracetam has anti-nociceptive effects and its mechanisms. Per oral pretreatment with piracetam reduced in a dose-dependent manner the overt pain-like behavior induced by acetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 52 publications
3
33
0
1
Order By: Relevance
“…In addition to 5-HT and NE reuptake inhibitors, nootropic agents like piracetam [16] also play an important role in cognition. The dose range of piracetam described in package inserts of Nootrpil® is 2.4~12 gm per day [17]. The resulting dose range would be 34 to 171 mg/kg for an adult of 70 kg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to 5-HT and NE reuptake inhibitors, nootropic agents like piracetam [16] also play an important role in cognition. The dose range of piracetam described in package inserts of Nootrpil® is 2.4~12 gm per day [17]. The resulting dose range would be 34 to 171 mg/kg for an adult of 70 kg.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting dose range would be 34 to 171 mg/kg for an adult of 70 kg. Navarro et al [17] showed therapeutic activity of piracetam at 100 mg/kg dose. Therefore, piracetam monotherapy was considered at 100 mg/kg dose in present study.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in lipid peroxidation is accompanied by T‐cell inhibition, with the latter inducing the normalisation of immunity by decreasing lipid peroxidation . Piracetam also has analgesic effects , reducing thermal hyperalgesia induced by tumour necrosis factor‐α (TNF‐α) . This property of the drug could be helpful in decreasing painful stimuli in skin burns.…”
Section: Discussionmentioning
confidence: 99%
“…Piracetam also favours the normalisation of immunity by effecting lipid peroxidation . In addition, it reduces peripheral inflammation and decreases neuropathic pain and thermal hyperalgesia .…”
Section: Introductionmentioning
confidence: 99%
“…The levels of lipid peroxides were expressed as nmoles of malondialdehyde (MDA) formed per mg -1 protein. Protein concentration was determined as described by Navarro et al (16). Crystalline bovine serum albumin was used for calibration curve.…”
Section: Determination Of Lipid Peroxidationmentioning
confidence: 99%